2013
DOI: 10.1007/s10529-012-1128-8
|View full text |Cite
|
Sign up to set email alerts
|

Differential alkaloid profile in Uncaria tomentosa micropropagated plantlets and root cultures

Abstract: The alkaloids of Uncaria tomentosa micropropagated plantlets and root cultures were isolated and identified by NMR and mass spectrometry. Plantlets yielded pteropodine (1), isopteropodine (2), mitraphylline (3), isomitraphylline (4), uncarine F (5), speciophylline (6), rhynchophylline (7) and isorhynchophylline (8). In plantlets growing under continuous light, tetracyclic alkaloids 7 and 8 decreased from 20 ± 1.8 at 2 months to 2.2 ± 0.33 mg/g dry wt at 6 months, while the pentacyclic alkaloids 1-4 increased f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
23
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 15 publications
(25 citation statements)
references
References 24 publications
1
23
0
1
Order By: Relevance
“…The content of tetracyclic alkaloids is higher in younger seedlings, whereas the pentacyclic alkaloids accumulate more in older plants (LUNA-PALENCIA et al, 2013).…”
Section: Developmentmentioning
confidence: 92%
See 2 more Smart Citations
“…The content of tetracyclic alkaloids is higher in younger seedlings, whereas the pentacyclic alkaloids accumulate more in older plants (LUNA-PALENCIA et al, 2013).…”
Section: Developmentmentioning
confidence: 92%
“…In this context, various descriptions of in vitro insertion of U. tomentosa are available. However, a micropropagation protocol showing the production viability on a commercial scale, e.g., using a temporary immersion system was not yet published (FERIA-ROMERO et al, 2005;PEREIRA et al, 2006;LUNA-PALENCIA et al, 2013).…”
Section: Developmentmentioning
confidence: 99%
See 1 more Smart Citation
“…Root cultures of U. tomentosa (line Utr-3) arising from micropropagated plantlets (Luna-Palencia et al, 2013) were grown in 250-mL Erlenmeyer flasks (covered with aluminum foil) with 100-mL of MS medium (Murashige and Skoog, 1962), 2% sucrose without plant growth regulators and pH 6.4 adjusted prior to sterilization. The cultures were incubated at 25 ± 2 • C, using orbital agitation at 110 rpm, and under continuous light intensity 13 µmol m −2 s −1 .…”
Section: Root Cultures and Elicitationmentioning
confidence: 99%
“…This plant produces the highly oxidized monoterpenoid oxindole alkaloids (MOA) isopteropodine, mitraphylline, isomitraphylline and rhynchophylline, which exhibits immunomodulatory, anti-AIDS, cytotoxic, and antileukemic properties (Laus, 2004). In previous work, it was found that root suspension cultures of this species produced MOA and accumulated 3α-dihydrocadambine (Huerta-Heredia et al, 2009), a glucoindole alkaloid with hypotensive and antioxidant activities (Endo et al, 1983) and dolichantoside (Luna-Palencia et al, 2013), a N-β-methylated strictosidine with potent anti-malarial effect (Frédérich et al, 2000). Moreover, the antioxidant response and alkaloid production stimulation have been correlated with oxidative stress (Trejo-Tapia et al, 2007) triggered by H 2 O 2 treatment (HuertaHeredia et al, 2009;Vera-Reyes et al, 2013) and by combined addition of the glutathione inhibitor, buthionine sulfoximine and jasmonic acid (Vera-Reyes et al, 2013).…”
Section: Introductionmentioning
confidence: 99%